Synthesis of the Data on COVID-19 Skin Manifestations: Underlying Mechanisms and Potential Outcomes - Farinazzo E; Dianzani C; Zalaudek I; Conforti C; Grabbe S; Goldust M (Dove Medical Press, 2021)
Eleonora Farinazzo,1 Caterina Dianzani,2 Iris Zalaudek,1 Claudio Conforti,1 Stephan Grabbe,3 Mohamad Goldust3 1Dermatology Clinic, Maggiore Hospital, University of Trieste, Trieste, Italy; 2Dermatology Section, Department of Plastic, Reconstructive and Cosmetic Surgery, Campus Biomedico University Hospital, Rome, Italy; 3Department of Dermatology, University Medical Center Mainz, Mainz, GermanyCorrespondence: Mohamad GoldustDepartment of Dermatology, University Medical Center of the Johannes Gutenberg University, Mainz, GermanyTel +49 1786-97-425Fax +49 6131-17-6629Email mgoldust@uni-mainz.deAbstract: The incidence of coronavirus disease 2019 (COVID-19)-related skin manifestations has progressively grown, in parallel with the global severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spreading. The available evidence indicates that cutaneous signs are heterogeneous and can be divided as follows: a) erythematous rashes, b) lesions of vascular origin, c) vesicular rashes, d) urticarial rashes, and e) acute generalized exanthematous pustulosis (AGEP), erythema multiforme (EM) and other polymorphic/atypical reactions. Most cutaneous manifestations appear simultaneously or after respiratory and/or systemic symptoms such as fever, even if rarely urticaria has been reported as the first sign of the disease. It has been proposed that erythematous and vesicular rashes, as well as urticaria, are the result of immunological activation against Sars-CoV-2, similarly to other viral exanthems; alternatively, reactivation or co-infection of herpesviruses and drug hypersensitivity represent possible etiologic diagnosis that has to be considered. Regarding lesions of vascular origin, ischemic ones are the result of systemic hypercoagulability established in severe infections, whereas chilblains seem to be linked to the type I-interferon massively produced to halt virus replication. AGEP is triggered by drugs, whereas EM could represent a delayed immune response to the virus or a hypersensitivity reaction to drugs elicited by the inflammatory process built to fight the infection. A further pathogenic hypothesis is that the virus, or its particles detected in the skin (particularly in endothelium and eccrine glands), could be responsible for certain skin reactions, including chilblains and EM. From the available data, it appears that chilblains are correlated with younger age and less severe disease, while ischemic manifestations occur in the elderly with severe infection. In conclusion, larger studies are needed to confirm the suggested pathogenetic mechanisms of COVID-19-related skin reactions and to determine the potential prognostic significance of each one.Keywords: COVID-19, skin rashes, SARS-CoV-2, cutaneous manifestations